(untitled) (The Journal of Psychology and Sociology, 2020)
The article analyzes the experience of preparing students for project activities in the University. Training in project, design and innovation, design and research activities as a way to solve professional problems is considered as one of the priorities of modern education. Analysis of project-oriented technologies used in higher education institutions of Western Europe and the United States in the preparation of engineering specialists in General leads to the conclusion that despite the features inherent in each educational system, there are a number of identical characteristics, such as the presence of a professionally significant task; organization of work in a team; the leading role of the teacher not only as an inspirer and consultant, but also as a role model; interdisciplinary nature of projects. These achievements inspire countries in other regions of the world to pay more and more attention to project-based learning. The article considers the accumulated in the Commonwealth of Independent States no less important experience in the organization of project activities of students in this aspect. On the basis of the analysis it is proved that special opportunities are opened by project activity in the Union with e-learning. An in-depth review of the research of Russian scientists on the organization of project activities in the educational environment, including the analysis of what gives the inclusion of students in the project activities. Considering the Kazakh experience of preparing students for project activities in the University, at-tention is drawn to the fact that students are actively involved in youth social projects. The activity of al-Farabi KazNU is deeply analyzed on the organization of project activities of students at the University, faculty, Cathedral levels and in the forms of social, research, creative, leisure projects. The analysis of foreign and domestic experience of preparing students for project activities in the University, shows that the process of formation of project competence of students is a purposeful and organized process of mastering by students the knowledge, skills and experience necessary for them for productive and personal – meaningful implementation of project activities, allowing to develop a wide range of competencies necessary for life in today’s dynamic socio-economic conditions. Key words: project planning, project competence project activities, innovative education, project team, project teamwork, project-based learning, design research, design thinking style.